EDUCATION AND RESEARCH AS COMPONENTS OF INDONESIA DEFENSE DIPLOMACY - Midhio, I Wayan; Priyono, Juniawan (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2019)
Defense diplomacy seeks to build partnerships through the use of defense-related programs. The Government of Indonesia develops practical cooperation among regional and extra-regional defense establishments on areas of mutual concern in education and research. Indonesia assigns Indonesia Defense University (IDU) to provide professional graduate education in defense studies with strong practical and area emphasis, conduct relevant research in defense strategy and management, national security and defense technology. Heads of Defense Universities/Colleges/Institutions Meeting (HDUCIM) serves the exchange of information concerning curriculum, defense concepts, and state defense development; it is also possible to conduct cooperation on research. In promoting regional security, defense diplomacy through education and research could play an important role in posing the stability of interstate relations by illustrating the relations between Indonesia-Cambodia and Indonesia-Philippines.Â Â Â